2021
DOI: 10.21203/rs.3.rs-477805/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional Status in Relation to Depression Among Elderly Individuals in Indonesia

Abstract: Background: Depression among elderly individuals is related to physical illness, functional status, prolonged treatment and other factors. Depression is not effectively treated with medication but can be alleviated by treating the physical illness and improving functional status. Therefore, this study aims to determine the relationship between functional status and depression in elderly individuals in Indonesia.Methods: The data used were obtained from a national survey dataset, namely, the Basic Health Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(25 reference statements)
1
1
1
Order By: Relevance
“…The results also showed that when the score of functional disability in ADL and IADL increases, the person's depression score decreases, which is consistent with the results of other studies (20,22,36,37).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results also showed that when the score of functional disability in ADL and IADL increases, the person's depression score decreases, which is consistent with the results of other studies (20,22,36,37).…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed a higher prevalence of depression compared to the studies conducted in China (12.2%), (2) (39) and study by Daiani and Indrawati in Indonesia (7.7%) (22). However, the prevalence of depression was lower than the studies by Nekar et al in India (68.5%) (15), the study by Rahanur Alam in Bangladesh (84%)(16), and the study by T. M. Dao in Vietnam (66.9%) (11).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation